Hubungan Keterlibatan Orang Tua dalam Pendidikan Keagamaan Anak dengan Hasil Belajar Kognitif - Nurul Rahmawati (Gunung Djati Conference Series, 2022)
The aims of the research are: (1) To determine student responses to parental involvement in children's religious education. (2) Knowing student learning outcomes in PAI subjects. (3) Knowing the relationship between students' responses to parental involvement with their cognitive learning outcomes at school. This study uses a quantitative approach with a descriptive correlation method. Data collection techniques are observation, interviews and questionnaires. The data analysis used is a statistical approach, namely partial analysis, normality test, homogeneity test and correlation test. The results showed that the relationship between student responses to parental involvement in children's religious education (variable X) with student cognitive learning outcomes in PAI subjects (variable Y) was in the medium category with a correlation coefficient of 0.46 which was in the interval 0.41-0, 60. The hypothesis is accepted, based on Tcount (=3.906) > Ttable (=2.008). That is, the more positive the student response to parental involvement in children's religious education, the better student learning outcomes in PAI subjects will be.